Clinical Characteristics and degree of severity of COVID-19 in Hemodialysis Patients in Armed Forces Institute of Urology. - Umar, Saba; Sabir, Sohail; Raja, Khalid; Mansoor, Khurram; Sajid, Tanveer; Saleem, Salman; Ikram, Aamir; Siddiqui, Fuad; Sabir, Haroon (Pakistan Journal of Kidney Diseases, 2021)
Introduction This study was conducted to evaluate the clinical characteristics and severity of COVID -19 in hemodialysis patients at from 1st March 2020 to 15th August 2020. Methodology It was a prospective and Cross Sectional Observational Study. We collected data prospectively that includes all patients on maintenance hemodialysis and reviewed clinical characteristics of those with laboratory-confirmed COVID-19 between March 1and August 15, 2020. Results 39 out of 268 dialysis dependent patients had COVID-19. Mean age of patients was 55.9yrs. Only 35.8% patients were symptomatic. 15 out of 39 were having mild disease,12 had moderate and 12 had severe disease. Females (54.5%) were found to be more affected than males(45.5%). Dry cough was the commonest symptom (53.8%) followed by fever (46.1%) and abdominal pain(18.1%). Patients with multiple comorbidities were found to have severe disease. Conclusion We concluded that patients receiving maintenance hemodialysis are susceptible to COVID-19 and that hemodialysis centers are high risk for spread of infection. Isolating patients with COVID-19 can help in preventing the spread of COVID-19.